Functional transcranial brain imaging by optical-resolution photoacoustic microscopy - Hu, Song (2009)
Optical-resolution photoacoustic microscopy (OR-PAM) is applied to functional brain imaging in living mice. A near-diffraction-limited bright-field optical illumination is employed to achieve micrometer lateral resolution, and a dual-wavelength measurement is utilized to extract the blood oxygenation information. The variation in hemoglobin oxygen saturation (sO(2)) along vascular branching has been imaged in a precapillary arteriolar tree and a postcapillary venular tree, respectively. To the best of our knowledge, this is the first report on in vivo volumetric imaging of brain microvascular morphology and oxygenation down to single capillaries through intact mouse skulls. It is anticipated that: (i) chronic imaging enabled by this minimally invasive procedure will advance the study of cortical plasticity and neurological diseases; (ii) revealing the neuroactivity-dependent changes in hemoglobin concentration and oxygenation will facilitate the understanding of neurovascular coupling at the capillary level; and (iii) combining functional OR-PAM and high-resolution blood flowmetry will have the potential to explore cellular pathways of brain energy metabolism.